Glomus Tumor in the Left Submandibular Region: A Rare Case Report and Literature Review - Huan Liu; Chengyao Zhu (Cancer Reports)
ABSTRACT Background Glomus tumors are rare, benign mesenchymal neoplasms predominantly located in subungual regions of the extremities. Their occurrence in the mandibular region is exceptionally uncommon, presenting unique diagnostic challenges. Only a limited number of submandibular glomus tumors have been documented, leaving their presentation and management largely underexplored. Case We presented a case of glomus tumor in the submandibular area of a 60‐year‐old female, which appeared as a purplish‐red lesion. In the absence of characteristic symptoms such as tenderness and cold sensitivity, the lesion was initially misdiagnosed as a pigmented nevus. Histopathological analysis subsequently confirmed the diagnosis as a glomus tumor. Immunohistochemical (IHC) staining further confirmed the tumor's smooth muscle and mesenchymal origins, with positive for Vimentin, SMA, Syn, Actin, Desmin, and CD34. The patient underwent surgical tumor excision with no recurrence after 28 months of follow‐up. Conclusion This case underscores the importance of considering glomus tumors in atypical locations and highlights the need for a comprehensive diagnostic approach to prevent misdiagnosis. Surgical excision remains the primary treatment, with extended postoperative surveillance recommended to monitor for recurrence.